Analisis Pemanfaatan Lampu LED di Industri Pupuk Terhadap Konsumsi Energi dan Efisiensi Biaya Listrik - Himmatul Aliyah Rosydi; Firra Rosariawari (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Along with the current developments, electricity has become a basic need that must be required. With population growth, economic development, and an increase in various activities and the use of facilities that require electricity, the use of electrical energy will continue to increase even in the use of lights as lighting in offices. The expected purpose of this study is to examine the efficiency of energy use as office lighting for one of the fertilizer industries before and after using LED lights, as well as analyze the costs incurred and the economic value obtained from the use of LED lamps. In this study, several data are needed, such as building plan data, inventory of the types of lamps used, electrical energy consumption, and the price of electricity consumption per kWh through the calculation method. The difference in costs incurred for the use of non-LED lamps into LED lamps is IDR 580,931.14 in the 1st-floor office building in one of the fertilizer industries and IDR 319,747.56 in the 2nd-floor office building in one of the fertilizer industries. Based on this, the difference in costs incurred is very large, so the use of LED lamps is the main alternative in saving energy and costs. Therefore, it is important to conduct studies and research on the impact that can be caused by the use of LED lights on energy consumption and electricity cost efficiency in the company.